Evaluating Resistance to Acetyl Salicylic Acid Using Platelet Function Test in Patients with Ischemic Stroke at Cipto Mangunkusumo Hospital - M. Kurniawan; Salim Harris; Deddy Hermawan; Joedo Prihartono (Acta Medica Indonesiana)
Aim: to identify the prevalence of laboratoric ASA resistance using platelet function tests in patients with ischemic stroke at Cipto Mangunkusumo Hospital and its associated factors. Methods: this study was a cross-sectional study involving 50 patients with ischemic stroke who only received ASA treatment. Evaluation of resistance to ASA was performed using Verifynow® platelet function test. ASA resistance was defined as ASA reaction unit (ARU) ≥550. Results: there were 7 patients with ASA resistance. The mean age of subjects in ASA resistance group was 51.3±9.2 years; while in ASA responsive group was 57.8±9.7 years. In ASA resistance group, there were 85.7% male patients, 57.1% active smoker and 100% subjects with hypertension. Conclusion: the prevalence of laboratoric ASA resistance in patients with ischemic stroke evaluated using platelet function test at Cipto Mangunkusumo Hospital is 14%. The prevalence is more likely to occur in male patients who were active smoker, at younger age and with comorbidity of hypertension.